2000
DOI: 10.1053/jhep.2000.17738
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Promotes Cell Survival From Fas-Mediated Cell Death in Hepatocellular Carcinoma Cells via Akt Activation and Fas-Death–Inducing Signaling Complex Suppression

Abstract: The Akt/PI-3 kinase pathway is a system essential for cell survival. In the current study, we showed that hepatocyte growth factor (HGF) activates the Akt/PI-3 kinase pathway to suppress Fas-mediated cell death in human hepatocellular carcinoma (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 45 publications
8
70
0
1
Order By: Relevance
“…23 Both PI-3Kinase/Akt and JAK/STAT signaling are activated by these growth factors in a number of cell types. 24 Consistent to results using other cell types, we have shown that these pathways are induced after EGF/HGF treatment in primary human hepatocytes isolated from several donors. These results are supported by recent work showing induction of STAT3 after HGF treatment in primary human hepatocytes contributes to reduced response to CD95 stimulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…23 Both PI-3Kinase/Akt and JAK/STAT signaling are activated by these growth factors in a number of cell types. 24 Consistent to results using other cell types, we have shown that these pathways are induced after EGF/HGF treatment in primary human hepatocytes isolated from several donors. These results are supported by recent work showing induction of STAT3 after HGF treatment in primary human hepatocytes contributes to reduced response to CD95 stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…These results are supported by recent work showing induction of STAT3 after HGF treatment in primary human hepatocytes contributes to reduced response to CD95 stimulation. 24 The physiological relevance of our findings are supported by the fact that the levels of HGF we found in some of the patients approached the dose of HGF used in vitro on isolated human hepatocytes for achieving protection against apoptosis signaling induction.…”
Section: Discussionsupporting
confidence: 63%
“…26,39 Activation of PI3-kinase and Akt also inhibits Fas receptor-mediated cell death in hepatocytes. 40,41 Therefore, under the context of a constitutive Fas receptor expression in HSC/ MFB, 35 Gas6 could protect these cells and macrophages against apoptosis in vivo during tissue repair. It may favor a transient accumulation of these cytokine-and matrixproducing cells, which are necessary to the reorganization of liver architecture and hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor tyrosine kinase (RTK) is predominantly expressed on epithelial and endothelial cells and regulates proliferation (Efimova et al, 2004), migration (Monvoisin et al, 1999), cell survival (Suzuki et al, 2000), morphogenesis , angiogenesis (Schmidt et al, 1995), as well as tissue regeneration (Borowiak et al, 2004). Hepatocyte growth factor binding and MET multimerization results in receptor auto-and paraphosphorylation of adaptor proteins (e.g.…”
Section: Transforming Growth Factor B Signaling Axismentioning
confidence: 99%